Pengembangan Bahan Ajar Sistem Peredaran Darah Manusia Berbasis Electronic Book Terintegrasi dengan Virtual Labs untuk Siswa Kelas XI IPA SMA - Ilmi R.H, Nurul; Nurhayati B, Nurhayati B; Adnan, Adnan (Biology Teaching and Learning, 2020)
Abstract. Teaching materials for electronic blood circulation systems based on electronic books were developed based on the lack of learning resources and media available in schools. This product development will make students learn independently and use learning resources that can be used anytime and anywhere. This study aims to produce products in the form of teaching materials for electronic bookbased circulatory systems in which there are media in the form of text, images, videos, virtual labs that are done through e-learning media (bioedukasi.com) and are valid. Electronic book-based teaching material developed using the Kvisoft application so that the display of teaching materials is like a printed book in general. The fundamental differences in teaching materials developed have a variety of media in the form of videos that can be played directly in teaching materials. The development research model conducted refers to the four D (4D) model initiated by Thiagarajan. Model four D (4D) consists of the defining stage (define), the design phase (design), the stage of development (develop) and the stage of deployment (disseminate). Based on the research results obtained that the product in the form of teaching materials based on electronic books and e-learning media (bioedukasi.com) is valid. The valid value of the teaching material obtained is 4.36 while the valid value of e-learning is 4.43. The two products produced are valid so it is feasible to use. Keywords: teaching materials, electronic books, virtual Labs, elearning